Physicochemical Characterization of Polysaccharide–Protein Carriers with Immobilized Yeast Cells Obtained Using the Freeze-Drying Technique - Nataša Obradović; Bojana Balanč; Ana Salević-Jelić; Mina Volić; Verica Đorđević; Mirjana Pešić; Viktor Nedović (Foods)
New techniques for the immobilization of yeast cells have the potential for enhancement of the beer production process. Alongside conventional materials for cell immobilization, there is a rising trend toward polysaccharide–protein systems. This study focused on the immobilization of yeast cells (Saccharomyces pastorianus) via a freeze-drying process. The whey protein isolate, sodium alginate, maltodextrin, inulin, and their blends were used for carrier preparation. The effect of a 1.0% inulin solution as a cryoprotectant on the viability of the yeast cells after the freeze-drying process was also analyzed. The powders were assessed for cell viability, moisture content, water activity, solubility, particle size, and surface charge. According to the results, the addition of whey proteins reduced the moisture content, while solubility did not significantly decrease. Samples containing whey protein showed slight diameter variations. The negative surface charge observed in all samples, especially the control, indicates a cell’s tendency to aggregate, demonstrated by optical microscopy. SEM micrographs showed successful cell immobilization in polysaccharide–protein carriers. Furthermore, inulin and whey protein addition enhanced cell protection during the immobilization of cells. The freeze-drying technique demonstrates efficacy in immobilization of yeast cells, indicating its potential for applications in the food and beverage industry.